Distribution and Damage of African Citrus Psyllids (Trioza erytreae) in Casimiroa edulis Producing Areas of the Eastern Zone of Ethiopia. - Hailu, Tesfaye; Wakgari, Mulatu (International Journal of Environment, Agriculture and Biotechnology, 2019)
The common white sapote, Casimiroa edulis occurs both wild and cultivated in central Mexico and produced in a different part of Ethiopia as home garden fruit crop for consumption as food. People also consider the fruits as one of the stimulant fruit crop. Currently, African citrus psyllids (Trioza erytreae) became one of the important pests of C. edulis in Ethiopia. The distribution and severity of this pest were recorded with an irregular pattern in the eastern part of Ethiopia. From all surveyed area (except some districts of Dire Dawa), very high infestation with high population density were recorded. The pest is currently in Ethiopia. This is first record of Trioza erytreae as devastating pest of casimir trees in Ethiopia. It is worth reporting to promote coordinated efforts amongst stakeholders, research specialists and extension officers to create awareness for proper management of the pest.